Procedural Logic Gaps in Mitigation Mapping: Content Analysis of QGIS-Based Essay Responses - Suci Handayani; Eko Hariyono; Binar Kurnia Prahani; Muhammad Satriawan; Parizal Hidayatullah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Theoretical knowledge about disasters does not always correspond to technical ability in mapping risks. Lombok Island has high tectonic complexity because it is flanked by the Sunda Subduction Zone in the south and the Flores Back-Arc Thrust in the north, which requires precise spatial data-based mitigation strategies. This study aims to reconstruct students' mental models in integrating geospatial technology and disaster content through content analysis of essay answers. The novelty of this study lies in revealing the 'procedural logic gap' that is often overlooked in menu-driven practical assessments. The method used is descriptive-qualitative with a content analysis approach on 35 students of the Physics Study Program who have taken the Mapping course. The analysis framework adopts the Geospatial Technology Competency Model (GTCM) and the SOLO Taxonomy. Research results reveal a sharp cognitive polarization, where the majority of respondents (60%) are at the Pre-structural and Uni-structural levels. Key findings indicate the phenomenon of "Disconnected Cognition"; students understand the conceptual aspects of tectonics (Tier 3 GTCM), yet fail to construct a systematic QGIS workflow (Tier 4 GTCM), which is reflected in fragmented procedure descriptions. The inability to integrate this operational logic causes mitigation map outputs to become merely "visual decorations" without optimal function as a decision-making tool. This study recommends a repositioning of the GIS curriculum to emphasize strengthening system logic rather than merely imitating software procedures.